The Influence of Leadership and Professionalism to the Performance of Teachers of SMAN 1 Teluk Kuantan - Anggun Putri Rosi; Nuryanti '; Kurniawaty Fitri (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2014)
In the face of stiff competition in the world education, SMAN 1 Teluk Kuantan strive to improve the quality of school, including by improved performance of teachers with pay attention to the factors of leadership and professionalism. Being a teacher without good leadership and professionalism will make teacher performance is reduced and planning or target is not reached.Sampling in this study conducted a census in which all members of the population sampled then obtained 49 samples. Research done by giving questionnaires to be filled up to all the teachers at SMAN 1 Teluk Kuantan, then the results were analyzed qualitatively and quantitatively as well as partial and simultaneous (multiple regression analysis with SPSS).The analysis showed that there is a significant and positive effect between the variables of leadership and professionalism of the teacher’s performance in SMAN 1 Teluk Kuantan either partially or simultaneously. The most dominant variable in affecting the teacher’s performance is professionalism. Of the conclusions that have been obtained, the researchers gave some suggestion in this research that teachers are expected to keep increasing the motivation and skills to advance education, always develop insight expertise and knowledge through a variety of media education. In addition, the principal of SMAN 1 Teluk Kuantan to be more assertive in the discipline or teachers.Keywords: Performance of Teachers, Leadership, Professionalism.